First Report of Sarcocystis pilosa from a Red Fox (Vulpes vulpes) Released for the Re-Introduction Project in South Korea - Yeonghoon Jo; Sook Jin Lee; Mohammed Mebarek Bia; Seongjun Choe; Dong-Hyuk Jeong (Animals, 2023)
The red fox (Vulpes vulpes) is a known host for various parasites, including numerous helminths and protozoans. Among these, certain species in the genus Sarcocystis (phylum Apicomplexa) have been documented to possess the capability to infect red foxes as definitive hosts. In South Korea, red foxes have been introduced and released as part of a re-introduction program. However, two months after its release, one of the foxes was found dead because of illegal trapping. The fox was necropsied, and a subsequent coprological study revealed oocysts of Sarcocystis sp. in the intestinal contents. The oocysts were identified as Sarcocystis pilosa based on the 18S rRNA and cytochrome c oxidase subunit 1 (cox1) gene sequences. It exhibited a 99.7–100% identity with 18S rRNA gene sequences and 99.1–99.8% identity with cox1 gene sequences from other previously reported S. pilosa samples. Additionally, it showed identities of 95.4–96.4% and 91.1–91.5% with the cox1 gene sequences of S. hjorti and S. gjerdei, while demonstrating 99.6 and 98.1% identity with the 18S rRNA gene sequences of S. hjorti and S. gjerdei, respectively. This is the first report from mainland Asia, excluding the Japanese archipelago, indicating that the life cycle of S. pilosa persists in South Korea.